Pencegahan Ulkus Dekubitus pada Pasien Bedrest di Ruang High Care Unit (HCU) Unit Stoke RSUD dr. Soediran Mangun Sumarso Wonogiri - Alvin Kiky Lutviana; Anis Siyama; Putri Meliana; Anung Kurniawan Ardi; Adinda Putri Fatikha; Aldilla Nurhaliza; Ida Nur Imamah (Dinamika Sosial : Jurnal Pengabdian Masyarakat dan Transformasi Kesejahteraan, 2024)
The level of knowledge of the patient's family in the Stroke Unit at RSUD dr. Soediran Mangun Soemarso regarding "Prevention of Decubitus in Bedrest Patients in the Stroke Unit of Dr. Soediran Mangun Sumarso Wonogiri Hospital" is still quite low. Therefore, the group carried out PKM health education regarding the prevention of decubitus ulcers in bedrest patients in order to increase the knowledge of the patient's family in the Stroke Unit of RSUD dr. Soediran Mangun Soemarso Wonogiri. The activity target to be achieved from this activity is 100% of patient families in the Stroke Unit of RSUD dr. Soediran Mangun Soemarso Wonogiri who attended the event knew and understood how to prevent decubitus ulcers in bed rest patients.